Structure of Tax Equilibria - Fuchs, Gerard; Guesnerie, Roger (Econometrica, 1983)
[The paper considers a world in which one public good is financed by commodity taxes. It concentrates on the global study of the set of tax equilibria (corresponding to any possible taxation scheme). In particular conditions for "regularity" and connectedness of this set are exhibited. Consequences obtain both for the positive theory of tax incidence in general equilibrium (existence, continuity, uniqueness) and for normative theory ("regularity" of optimal solutions, algorithms of tax reform...).]